The East African HIV prevention model: Perspectives from HIV-positive male immigrants living in the USA - Jennifer Jo Connor; Sharon M. Lund; Amanda Ciesinski; Megan Finsaas; Tom Bichanga; Beatrice “Bean” E. Robinson (Cogent Medicine, 2016)
African-born immigrants have been identified as a high risk population for contracting HIV/AIDS. We used Community Identification processes to interview three types of respondents: 11 HIV-seropositive East African-born men; 11 professionals working with HIV-seropositive East African-born men; and 11 individuals interacting with HIV-seropositive East African-born men. Using grounded theory methodology, we developed the East African HIV Prevention Model which displays four components (demographic factors, stigma, disclosure, education) contributing to high risk behaviors and HIV testing. Our model suggests interventions for targeting community demographic factors, pervasive stigma leading to lack of disclosure, and education in the East African community.